Growth Performance of Three Exotic Pine Species in Relation to Indigenous Species in Uttarakhand Himalayas, India - Sharma, Neeraj Kumar; Chandran, Manoj; Bhatt, Jitendra (Indian Forester, 2009)
Growth and suitability of three exotic pine species - Pinus patula, P. greggii and P. elliottii were studied in Uttarakhand Himalaya and comparison made with the principal indigenous species, P. roxburghii (Chir pine). Exotic pines had significantly higher (p< 0.001) growth, volume production, increment and relative growth rate compared to P. roxburghii at 35 years of age. Exotic pines had greater growth rate in the initial 15 years than Chir pine. Thereafter, height and diameter growth rate of exotic pines reduced compared to Chir pine. This indicates the suitability of these exotic pines as short rotation, density plantation in order to maintain environmental stability.